Kalam Science Learning Strategies for Beginners - Achmad Habiburrohman; Imam Makruf; Muhammad Nanang Qosim (al-Afkar, Journal For Islamic Studies, 2025)
Kalam Science Learning Strategies for Beginners explains the importance of teaching Maharah al Kalam (speaking skills) in Arabic, especially for beginners. It aims to improve students' speaking skills through various creative and innovative techniques and approaches. This study outlines the stages in learning Maharah al Kalam, which include the stages of stimulation, thinking, processing words, and speaking them. Stimuli can be in the form of questions or images that trigger students to speak. Furthermore, students are expected to collect and organize their ideas before processing them into sentences that are in accordance with Arabic language rules. Supporting factors in this learning include correct pronunciation, adequate vocabulary, and understanding of grammar. The teacher acts as a facilitator who helps students understand the material and provides opportunities for discussion. In addition, the use of media such as textbooks, reading materials, and technology is also expected to enrich students' learning experience. In conclusion, teaching Maharah al Kalam at the beginner level requires a systematic approach and a variety of techniques to increase the effectiveness of learning, so that students can gain optimal Arabic language skills.